Prediction of failure of sands under constant volume general cyclic simple shear loading using specific dissipated energy - Zavala Rosell, Guillermo José (2023)
Seismic soil liquefaction is a recurring phenomenon that may cause significant damage to infrastructure during earthquakes and that in turn may also cause injuries and even fatalities. This phenomenon has been widely studied by researchers, and for its study the laboratory characterization of behavior of sands when subjected to cyclic loading is very important. One of the approaches for this kind of studies is through the calculation of the energy that is dissipated by the soil when it is subjected to cyclic loading. One of the hypotheses for utilizing these energy methods states that the cumulative dissipated energy required in a soil to reach failure only depends on the initial state of the sample (relative density and initial vertical effective stress) and should be reasonably constant and independent of the loading amplitude and waveform applied to the sample. This thesis work seeks to evaluate the validity of this hypothesis. Also, based on this hypothesis, it seeks to develop a simplified methodology to predict failure of sands when subjected to general cyclic loading, performing only simple harmonic tests. The hypothesis for the development of this methodology is that there is a relationship between the initial state of the sample and the cumulative dissipated energy to failure in cyclic simple shear test. To reach these goals, over 250 uniform and non-uniform constant volume cyclic simple shear tests were performed on Ottawa 20/30 sand, and the dissipated energy to failure was measured in each of these tests. The experimental program showed that the measured cumulative dissipated energy to failure was reasonably constant for the same initial sample conditions, but with some variability inherent to geotechnical laboratory testing. As expected, the cumulative dissipated energy increased with increasing initial stress level and relative density. Also, a simplified method to predict the dissipated energy to failure of a sample subjected to general cyclic loading, based on a multivariable regression performed on a simplified set of laboratory results, is presented, and it is next validated with two independent data sets. In both cases the method was found to yield reasonable predictions of failure of sands when subjected to complex and irregular cyclic shear loading.